2011
DOI: 10.1111/j.1365-2125.2011.03923.x
|View full text |Cite
|
Sign up to set email alerts
|

Slow‐release oral morphine for opioid maintenance treatment: a systematic review

Abstract: This review article summarizes the results of all available clinical trials considering the use of slow-release oral morphine (SROM) for opioid maintenance treatment (OMT). All studies published up to October 2010 and assessing SROM for OMT in adult patients are included. Three independent reviewers assessed the selected articles using a standardized checklist. Study design, study length and number of subjects included were recorded. Data about retention rate (proportion of participants remaining under mainten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…Considering the wide range of doses described in the literature, 65 we suggest that practitioners holding a federal exemption with no prior experience in prescribing slow-release oral morphine for opioid agonist treatment also consult with a specialist. As is the case with methadone, because of patient and public safety risks associated with slow-release oral morphine diversion, the committee suggests that the standard should be to prescribe slow-release oral morphine as daily witnessed doses.…”
Section: In Patients For Whom First-and Second-line Treatment Optionsmentioning
confidence: 99%
“…Considering the wide range of doses described in the literature, 65 we suggest that practitioners holding a federal exemption with no prior experience in prescribing slow-release oral morphine for opioid agonist treatment also consult with a specialist. As is the case with methadone, because of patient and public safety risks associated with slow-release oral morphine diversion, the committee suggests that the standard should be to prescribe slow-release oral morphine as daily witnessed doses.…”
Section: In Patients For Whom First-and Second-line Treatment Optionsmentioning
confidence: 99%
“…Moreover, overlap of two prescription forms is forbidden. Slow-release oral morphine sulfate (SROM) is now available as opioid maintenance therapy (OMT) in some European countries (Austria, Slovakia, Slovenia, Bulgaria, and Luxembourg), but not in France, where this prescription for OMT is off-labeled because of the lack of evidence showing that SROM is an effective alternative to methadone for OMT [6,7]. However, SROM can be prescribed in exceptional cases of intolerance or inefficacy of methadone or buprenorphine, as indicated by a note from the French General Directorate of Health in June 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Slow release morphine: Bulgaria, France, Italy, Luxemburg, Netherlands, Austria, Slovenia, and the United Kingdom allow treatment using slow release oral morphine (SROM) [91]. The use of SROM for maintenance treatment, however, remains controversial and scarcely studied.…”
Section: Methadonementioning
confidence: 99%
“…The use of SROM for maintenance treatment, however, remains controversial and scarcely studied. A recent literature review of the available clinical trials on the use of SROM concluded that there was currently no definite evidence showing that SROM is an effective alternate to methadone for opioid maintenance treatment [91].…”
Section: Methadonementioning
confidence: 99%
See 1 more Smart Citation